Double Valve-in-Valve Transcatheter Valve Replacements for Failed Surgical Bioprosthetic Aortic and Tricuspid Valves. Issue 3 (May 2019) - Lee, Kyongjune B.; Trachiotis, Gregory D.; Reiner, Jonathan S.; Nagy, Christian D.
Abstract : Transcatheter technology has revolutionized the treatment of valvular disease in the field of cardiology and cardiac surgery. We present an interesting case of a patient with prior double valve replacements, which had degenerated after a decade, with symptoms of decompensated heart failure. The patient was successfully treated with double valve-in-valve transcatheter aortic and tricuspid valve replacement.